2022
DOI: 10.1177/10600280221102557
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Diabetes Transitions of Care Clinic on Hospital Utilization and Patient Care

Abstract: Background There is currently limited guidance from the American Diabetes Association regarding transitions of care for patients with diabetes. Objective This study’s aim was to determine the impact of a diabetes-specific transitions of care clinic (TOCC) on hospital utilization and patient outcomes in recently discharged patients with diabetes. Methods This retrospective study evaluated patients seen by TOCC as compared with similar patients discharged from the study institution the year prior. The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As previously discussed, although this study did not show a change in readmission rates, current literature supports the use of a pharmacist integrated within a TOC service in reducing readmission to the hospital. Rinaldi et al 8 found that an interprofessional diabetes-focused TOC clinic, including an ambulatory care pharmacist, was effective in decreasing hospital utilization within 30 days of discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously discussed, although this study did not show a change in readmission rates, current literature supports the use of a pharmacist integrated within a TOC service in reducing readmission to the hospital. Rinaldi et al 8 found that an interprofessional diabetes-focused TOC clinic, including an ambulatory care pharmacist, was effective in decreasing hospital utilization within 30 days of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Rinaldi et al 8 demonstrated the effectiveness of a diabetes TOC clinic service on hospital utilization. They evaluated a model in which patients with a diagnosis of diabetes discharged were eligible for referral to the diabetes TOC clinic, regardless of their reason for admission.…”
mentioning
confidence: 99%
“…Individuals may be discharged to varied settings, including home (with or without visiting nurse services), assisted living, rehabilitation, or skilled nursing facilities. For individuals discharged to home or assisted living, the optimal discharge plan will need to consider diabetes type and severity, effects of the illness on blood glucose levels, and the individual's capabilities and preferences (29,152,153). See Section 13, "Older Adults," for more information.…”
Section: Diabetic Ketoacidosis and Hyperosmolar Hyperglycemic Statementioning
confidence: 99%